2014
DOI: 10.1177/1358863x14523063
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of acute limb ischemia in cancer patients

Abstract: The optimal management strategy for acute limb ischemia (ALI) in patients with a concomitant malignancy is not well established. A very high mortality rate (83-100%) at 1 year has been reported in those who are treated surgically. Accordingly, a conservative management approach has been suggested as the main therapeutic modality. Our aim was to evaluate the survival outcomes of cancer patients treated for ALI at our cancer center. Cancer patients treated for ALI at the MD Anderson Cancer Center from 2001 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…31 Decisions about the management of patients with malignancy should be individualised with the help of oncologists, as active treatment in selected patients can yield good results both from treatment of the leg and the cancer. 32,33 In a prospective study from Denmark with 26 years of follow up, patients with ALI and a newly diagnosed cancer had a higher risk of amputation than similar patients without cancer (hazard ratio [HR] 0.09 vs. 0.06), and patients with cancer also had a higher mortality rate (HR 0.67 vs. 0.37). 34 1.6.2.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…31 Decisions about the management of patients with malignancy should be individualised with the help of oncologists, as active treatment in selected patients can yield good results both from treatment of the leg and the cancer. 32,33 In a prospective study from Denmark with 26 years of follow up, patients with ALI and a newly diagnosed cancer had a higher risk of amputation than similar patients without cancer (hazard ratio [HR] 0.09 vs. 0.06), and patients with cancer also had a higher mortality rate (HR 0.67 vs. 0.37). 34 1.6.2.…”
Section: Epidemiologymentioning
confidence: 99%
“…For patients with acute limb ischaemia and underlying malignant disease, active revascularisation in selected patients should be considered, as the immediate postoperative outcome is comparable to patients without malignancy. 32 Tsang et al (2011), 33 Morris-Stiff and Lewis (2010), 31 Nicolajsen et al (2015) 34 clinical practice all six signs are rarely encountered, unless there is a severe ALI in a patient with otherwise normal arteries. Detection of peripheral pulses is enhanced by determination of the ABI using hand held Doppler.…”
Section: C Consensusmentioning
confidence: 99%
“…Degree of limb viability and associated co-morbidities greatly influence the decision whether to manage these patients operatively or non-operatively. No randomized studies are available due to the rarity of this presentation, however experience from the limited number of cases reported ( Table 1 ) and from studies involving patients with solid malignancies presenting with ALI, may guide decision making [ 4 , 41 ]. A conservative management approach has been advocated by some based on studies showing poor outcomes with post-operative mortality as high as 80%–100% when malignancy associated ALI is treated surgically [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A conservative management approach has been advocated by some based on studies showing poor outcomes with post-operative mortality as high as 80%–100% when malignancy associated ALI is treated surgically [ 42 , 43 ]. In contrast, recent retrospective studies have favored an early surgery-based limb salvage approach in malignancy associated ALI [ 4 , 41 ]. Mouhayar et al [ 41 ] reported a 47% amputation free survival in cancer patients with ALI when treated surgically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation